Revisiting our roots sources of stress and coping strategies of atis in Cati-cati, Guimaras. - Gomez, Keysie M.
This exploratory study aimed to identify the sources of stress and coping strategies of 16 married Atis (8 males, 8 females) who are living together with their partners in Sitio Cati-cati, Guimaras. Data were gathered through panunuluyan, pakikipagkwentuhan and pagtatanong-tanong using an interview guide for socio-demographic profile, 24-hour matrix, sources of stress, and coping strategies. , Results show that Atis identified family, basic needs, economic problems, community, and discrimination as their sources of stress. A combination of problem-focused and emotion-focused coping factors were applied by them.